2006
DOI: 10.1002/psc.778
|View full text |Cite
|
Sign up to set email alerts
|

I‐conotoxin superfamily revisited

Abstract: The I-conotoxin superfamily (I-Ctx) is known to have four disulfide bonds with the cysteine arrangement C-C-CC-CC-C-C, and the members inhibit or modify ion channels of nerve cells. Recently, Olivera and co-workers (FEBS J. 2005; 272: 4178-4188) have suggested that the previously described I-Ctx should now be divided into two different gene superfamilies, namely, I1 and I2, in view of their having two different types of signal peptides and exhibiting distinct functions. We have revisited the 28 entries present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The I-conotoxin superfamily was not included because there are still some debates about the classification scheme of the I superfamily. For example, some researchers shown that the conotoxins that were previously assigned to the I superfamily should be separated into two different gene superfamilies, namely I1 and I2 [7,18]. The remaining data set included 403 conotoxin sequences from A, M, O, and T superfamilies.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The I-conotoxin superfamily was not included because there are still some debates about the classification scheme of the I superfamily. For example, some researchers shown that the conotoxins that were previously assigned to the I superfamily should be separated into two different gene superfamilies, namely I1 and I2 [7,18]. The remaining data set included 403 conotoxin sequences from A, M, O, and T superfamilies.…”
Section: Datasetsmentioning
confidence: 99%
“…Because there are distinct characteristics such as highly conserved N-terminal precursor sequence, disulfidecrosslinked and similar mode of actions, conotoxins have been grouped into several different superfamilies, namely, A, I, M, O, T, P, S, J, D, V and C superfamily [1,7]. Each superfamily can further be classified into several families on the basis of the cysteine arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the proposed activity of GXIA is consistent with its observed non-paralytic effect. Whilst another I-superfamily member, ViTx1, has been reported to inhibit K V activity, based on theoretical modelling it is suggestive that ViTx1 acts as a pore blocker [19,53]. The obvious future direction will be to test the proposed biological activity of GXIA, as well as ion channel specificity and analyse whether the structural conservation to K V VS toxins translates into conserved pharmacological action.…”
Section: Electrostatic Surface and Proposed Activity As A Voltage Sensor Toxinmentioning
confidence: 99%
“…The disulfide-rich group, the conotoxins, is classified into superfamilies based on signal sequence homology and are further classified based on their disulfide framework and target. The I and the O superfamilies have been divided into distinct groups, I1, I2, O1, O2, and O3 [96][97][98] in the figure as a consequence of each having unique signal sequences. Although I1 and I2 have distinct signal sequences, they both have the same frameworks and targets.…”
Section: Cone Snails and Combinatorial Diversitymentioning
confidence: 99%